Liu Wei Di Huang Decoction Alleviates Renal Fibrosis by Inhibiting Endothelial Mesenchymal Transitions via Upregulating Sirt1 Expression and Inhibiting the Wnt/β-Catenin Signaling Pathway - Wang H; Chen SS; Zhang YX; Gao HB; Meng B; Wu WY; Tang Q (Drug Design, Development and Therapy)
Hui Wang,1,2 Shuang-Shuang Chen,1 Yong-Xian Zhang,2 Hai-Bo Gao,1 Bin Meng,1 Wei-Yu Wu,1 Qun Tang1 1Medical School, Hunan University of Chinese Medicine, Changsha, 410208, People’s Republic of China; 2The 960th Hospital of the PLA Joint Logistics Support Force, Jinan, Shandong, 250000, People’s Republic of ChinaCorrespondence: Qun Tang, Medical School, Hunan University of Chinese Medicine, Changsha, 410208, People’s Republic of China, Email tangqun460@126.comBackground: Renal fibrosis (RF) is the final outcome of chronic kidney disease (CKD), which can be triggered by various factors. Liuwei Dihuang Decoction (LWDHD) has been clinically established as an effective treatment for CKD, demonstrating anti-inflammatory, antioxidant, and antifibrotic effects. However, the specific molecular mechanisms underlying the therapeutic effectiveness of LWDHD remain unknown.Aim: Prediction of key active ingredients, targets, and mechanistic pathways of LWDHD in RF treatment.Materials and Methods: The bioactive components of LWDHD were identified and quantified using ultra-performance liquid chromatography-tandem quadrupole mass spectrometry (UHPLC-MS/MS). A network pharmacology approach was employed to predict the key targets of these bioactive components. A rat model of renal tubulointerstitial fibrosis was created through unilateral ureteral obstruction (UUO). Rats were divided into six groups: sham operation, UUO, low-dose LWDHD (LW-L), medium-dose LWDHD (LW-M), high-dose LWDHD (LW-H), and enalapril group. Continuous gavage of treatments was administered for 2 weeks. The renal tissues were histopathologically assessed, including HE, Masson’s trichrome, and Sirius red staining, immunohistochemistry, co-staining and Western blot analysis to evaluate the effects of LWDHD on renal fibrosis. Transforming growth factor beta-1 (TGF-β 1) was employed to stimulate endothelial-mesenchymal transition (EndMT) in EA.hy926 cells. The inhibitory effect of LWDHD on EndMT was validated through cellular morphology observations, Western blotting, and immunofluorescence assays.Results: LWDHD showed promise as a therapeutic agent by alleviating renal pathological injury and lowering collagen fiber accumulation. It enhanced Sirt1 expression while inhibiting the Wnt/β-catenin signaling pathway. Moreover, LWDHD increased the levels of the endothelial marker CD31 and decreased the expression of fibrosis-associated proteins, such as α-smooth muscle actin (α-SMA) and vimentin, thereby mitigating renal fibrosis.Conclusion: LWDHD has the potential to alleviate renal fibrosis, possibly through the upregulation of Sirt1, which inhibits the Wnt/β-catenin signaling pathway and thereby reduces EndMT.Keywords: renal fibrosis, LWDHD, network pharmacology, Sirt1, Wnt/β-catenin, EndMT